Mitochondrial Redox Hubs as Promising Targets for Anticancer Therapy - Ippolito, Luigi; Giannoni, Elisa; Chiarugi, Paola; Parri, Matteo (Frontiers in Oncology, 2020)
Mitochondria play a central and multifunctional role in malignant tumor progression. Beyond their bioenergetic role, mitochondria are essential for providing malignant cells a higher plasticity to face the harsh environmental conditions. Cell-autonomous metabolic deregulation of cancer cells, or metabolic adaptation to microenvironmental cues (lack of nutrients, stromal supply, hypoxia, etc.), represent the triggering event of mitochondria overexploitation in order to orchestrate nutrient sensing and upload, signaling and redox circuits. As readout of their higher function, mitochondria produce high levels of reactive oxygen species (ROS) that are integral to the regulation of different signaling networks driving proliferation, tumor cell survival and metastatic process. To compensate for the higher rate of mitochondrial ROS production, cancer cells have evolved adaptive mechanisms to increase their antioxidant systems and to address ROS to activate pathways useful for the tumor cell to counteract environmental changes. As these properties are critical for cancer progression, mitochondrial ROS have recently become an attractive target for anti-cancer therapies. We discuss how understanding of mitochondrial function in the tumor-specific generation of ROS will impact on the development of novel redox-based targeted therapeutic strategies.